Learning Style Profile of Students of The D-III Health Analysis Study Program in The Basic Microbiology Course at The University of Timur Indonesia - Rahmat Saleh; Suharsih Thahir; Asnurbaety Dwiyana (Universitas Negeri Makassar, 2026)
Abstract Purpose: This study aimed to describe the learning styles of Health Analyst students at the Faculty of Public Health, University of East Indonesia, and to identify the dominant learning style modality that may influence their learning process and academic achievement.Research Methodology: This study employed a survey research design with a quantitative descriptive approach. The research was conducted at the Faculty of Public Health, University of East Indonesia, during the 2025/2026 academic year. The population consisted of all Health Analyst students, while the sample included 35 students enrolled in the Basic Microbiology course. Data were collected using the VARK (Visual, Aural, Read/Write, and Kinesthetic) questionnaire developed by Neil D. Fleming. The questionnaire was used to assess students’ preferred learning modalities. Data analysis was carried out descriptively by calculating the percentage distribution of each learning style category.Results: The results showed variations in students’ learning style preferences. Among the four VARK modalities, the auditory learning style was identified as the most dominant learning style among Health Analyst students. This finding indicates that students tend to learn more effectively through listening, verbal explanations, discussions, and other auditory-based learning activities.Conclusions: The study concludes that auditory learning is the predominant learning style among Health Analyst students at the Faculty of Public Health, University of East Indonesia. Therefore, learning strategies that emphasize oral communication and interactive discussions may improve learning effectiveness.Limitations: This study was limited to a relatively small sample and involved students from only one study program and course.Contributions: The findings provide useful information for lecturers and curriculum developers in designing instructional strategies that align with students’ learning preferences and support more effective learning in health science education.Keywords: Learning styles, basic microbiology, learning